Acetic acid-catalyzed regioselective C(sp(2))-H bond functionalization of indolizines: concomitant involvement of synthetic and theoretical studies - Mane, Kishor D.; Mukherjee, Anirban; Das, Gourab Kanti; Suryavanshi, Gurunath (Journal of Organic Chemistry, 2022)
An atom economical and environmentally benign protocol has been developed for the regioselective C(sp2)-H bondfunctionalization of indolizines. The acetic acid-catalyzed cross-coupling reaction proceeds under metal-free conditions, producing awide range of synthetically useful indolizine derivatives. The present protocol showed good functional group tolerance and broadsubstrate scope in good to excellent yields. Quantum mechanical investigation using density functional theory (DFT) has played acrucial role in understanding that acetic acid is the key player in determining the actual pathway as the catalyst and its ultrafastnature. Different pathways involving inter- and intramolecular proton transfer, with or without acetic acid, were investigated.Calculated results revealed that a proton shuttle mechanism is involved for the least energetic, most favorable acetic acid-catalyzedpathway. Furthermore, regioselectivity has also been explained theoretically.

Regioselectivity in metalloradical catalyzed C-H bond activation: a theoretical study - Mukherjee, Anirban; Singh, Ritesh; Mane, Kishor D.; Das, Gourab Kanti (Journal of Organometallic Chemistry, 2022)
Pure quantum mechanical calculations were performed to find out the origin of regioselectivity under the metalloradical catalysis (MRC) by Co(II)-porphyrin, which showed regioselectivity is the inherent property of the aminyl radical generated from the sulfamoyl azide substrate. Different conformational analysis for the transition state from alpha-Co-III-aminyl radical to zeta-Co-III-alkyl radical formation have been studied to find out the most stable conformation for the preferable selectivity. The outcome of our study completely agrees with the reported experimental results. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: C-H activation; DFT; Metalloporphyrin; Metalloradical; Regioselectivity